A Primordial Ethnic Evaluation of Gurkhas of India (Intellectual Inception: A Multidisciplinary Research Journal of Bhojpur Campus, 2024)
The Gurkha people also known as Nepali people, renowned for their valor and loyalty in the world, have a longstanding historical presence in India. This paper through an in-depth analysis of historical recordsexamines the multifaceted ethnicidentity aspects of the Gurkha community's existence in India, encompassing their historical evolution, socio-cultural significance, and contemporary challenges.The research further investigates the contemporary challenges faced by the Gurkha community and uses a primordial lens to evaluate the unique identity and contributions of the Gurkha people in India. The Gurkhas' primordial identity fosters unity and cooperation, transcending geographical boundaries and creating a global shared identity. The concept of primordial ethnicity is crucial for understanding ethnic dynamics and cultural heritage's role in shaping their resilience. The Gurkhas' condition is influenced by historical experiences, economic opportunities, and political recognition, offering valuable insights into primordial ethnic identity.